HAMBATAN SISTER CITY KOTA SURAKARTA INDONESIA DENGAN KOTA ZHUHAI CHINA PASCA COVID-19 - Untari Narulita Madyar Dewi; Jehan Adhelia (Jurnal Dinamika Global, 2025)
The Government of Zhuhai Municipality, China, sent a health aid grant to the Government of Surakarta Municipality, Indonesia, in 2021. The health aid grant was sent to help tackle the escalataion of COVID-19 cases in Surakarta. The renewed status of the Coronavirus outbreak into a Public Health Emergency of International Concern (PHEIC) in 2020 requires a collective and also global response. The act of sending health grant was a further continuation of the Sister City partnership initiated in 2019. This article discussed the challenges of Surakarta and Zhuhai Sister City Partnership after COVID-19. The theory of Paradiplomacy and International Cooperation was applied in this article while performing the descriptive analysis benefitting the method of literature study to collect data. Results show that The Government of Surakarta Municipality faces some challenges in its role in the enforcement of Surakarta and Zhuhai Sister City Partnership.